Impact of DSA and immunosuppression minimization on rejection, graft, and patient survival after simultaneous liver–kidney transplantation - Dekeyser, Manon; Taupin, Jean-Luc; Elias, Michelle; Ichaï, Philippe; Herr, Florence; Boudon, Marc; Brunel, Melanie; Sa cunha, Antonio; Coilly, Audrey; Saliba, Faouzi; Durrbach, Antoine (Frontiers in Medicine, 2022)
Background: Acute rejection rate is low after simultaneous liver-kidney transplantation (SLKT), leading some groups to minimize immunosuppressive (IS) regimens. However, the impact of preformed (pDSA) or de novo donor-specific antibodies (dnDSA) on the graft remains unclear. Methods: We performed a retrospective analysis of 102 consecutive SLKT patients to study the impact of anti-HLA antibodies. Results: Anti-HLA antibodies were detected in 75 recipients (class I 23.8%, both classes I and II 23.8% and class II 14.3%). 42.8% of the patients had pDSA and 21.7% developed dnDSA. Overall patient survival at 1-3 and 5 years, was respectively 88%, 84% and 80%. Acute rejection occurred respectively in 3 (2.9%) liver and 6 kidney (5.9%) reciptients. pDSA with titers over 10,000 MFI (14.3%) was associated with lower patient survival (40% vs. 82%) but not with acute rejection. In a multivariable Cox regression analysis, the risk of death was associated with maleness, the highest titer of pDSA (p<0.0007) or the sum of pDSA >10000. Renal function did not differ between patients with class I pDSA (p = 0.631) and those with class II pDSA (p = 0.112) or between patients with and without a positive cross-match (p = 0.842). DnDSA were not associated with acute rejection, graft dysfunction or patient survival. IS minimization was not associated with rejection, graft dysfunction or death. Conclusion: In SLKT, high levels of pDSA > 10,000 were associated with lower patient survival, but not rejection or graft survival. Minimization of maintenance immunosuppression regimen was not associated with a poorer outcome.